Do metacommunities vary through time? Intermittent rivers as model systems. (20th August 2017) - Sarremejane, Romain; Cañedo‐Argüelles, Miguel; Prat, Narcís; Mykrä, Heikki; Muotka, Timo; Bonada, Núria
Abstract: Aim: Metacommunity assembly mechanisms have been traditionally considered stable through time. However, in highly dynamic systems with varying local environmental conditions and patch connectivity, communities are likely to experience temporal shifts in their assembly mechanisms. Here, we used a set of perennial (PR) and intermittent (IR) rivers to assess if assembly mechanisms vary seasonally in response to flow intermittence. Location: Mediterranean climate region (100, 000 km 2 ), Spain. Methods: We used a modelling approach to assess the relative effect of environmental sorting and dispersal‐based processes on aquatic invertebrate metacommunities within and across river types at four distinct hydrological periods. We used local environmental variables to assess environmental sorting, and considered geographical, network and topographical distances as different dispersal surrogates. Linear mixed effect models accounting for the non‐independence of pairwise distances were used to assess the relationships between community dissimilarity and distance matrices. Results: Assembly mechanisms were more temporally stable in PR than in IR. In PR, community dissimilarities were equally related to environmental and geographical distances suggesting codominance of species sorting and dispersal‐based assembly mechanisms. In IR, environmental distance best explained community dissimilarities during the dry period when flow cessation imposes strong environmental sorting, whereas metacommunity organization was much more stochastic during the rewetting period when high flows may randomly reorganize communities. Dispersal processes dominated assembly mechanisms between PR and IR during the rewetting period suggesting an increase in recolonization processes linking both river types following the dry period. Geographical and topographical distances best explained community variability, suggesting that overland dispersal dominates in river networks fragmented by drying events. Main conclusions: Aquatic invertebrate metacommunity assembly mechanisms vary seasonally in response to changes in hydrological conditions. The temporal dimension should be better incorporated into metacommunity studies in highly dynamic systems such as intermittent rivers.